Menganalisis Penyebab, Konsekuensi, Dan Solusi Potret Ketimpangan Ekonomi - Alif Finno Fidzaky; Verinda Yelanita; Muhammad Yasin (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Economic inequality is a complex phenomenon that occurs in various countries, including Indonesia. This research aims to analyze the causes, consequences and solutions of economic inequality. The causes of economic inequality are identified through various factors such as education, access to resources, government policies, and globalization. The consequences of economic inequality include broad social, political and economic impacts, including increased poverty, social instability and uneven economic growth. Proposed solutions include improving the education system, developing inclusive policies, empowering communities, and increasing access to basic services. This research underlines the importance of a multidimensional approach in addressing economic inequality to achieve sustainable and inclusive development.